Legal Consequences of Transferring Children’s Assets in Trusteeship Without Involving The Heritage Treasure Hall As Trustee - Sulistianingsih, Dewi; Sinaga, Dearni Meli Asih; Prasetyo Adhi, Yuli; Mohd Yusoff, Rahmawati (Faculty of Law Hang Tuah University, 2023)
The purposes of this research is to analyze legal ptotection for children in guardianship, which there is a transfer of assets in guardianship without involving Heritage Treasure Hall as supervisory trustees. The article will use a doctrinal research method to analyze the legal aspects of children guardianship. Guardianship is oversight of minors who are not under the authority of their parents so their legal position needs to be represented by a guardian. In a trusteeship, the guardian has rights and obligations over the life of the child under his guardianship and is responsible for the property of the child. In carrying out its role, under Article 366 of the Civil Code, the guardian is supervised by a supervisory guardian, in this case, the Heritage Treasure Hall. However, the Heritage Treasure Hall is less involved in trusteeship activities, especially in the transfer of children’s assets in trust. Actions that do not involve the Heritage Treasure Hall will result in the termination of a guardian and all actions that have been taken may be cancelled.